Implementation and experimental evaluation of a fast local mobility protocol - Ferreira, N. G. (2008)
In the current mobile cellular networks, the terminal mobility support is based on layer-1 and homogenous layer-2 mechanisms. This mobility support is sufficient for a moderate number of mobile terminals. However, in the future it is expected that this number will significantly increase and that distinct layer-2 interfaces will be available and required for the paradigm of ldquoInternet Everywhererdquo of the next generation networks. This paper presents the implementation and the evaluation results of a novel approach for local mobility in next generation networks. This mobility approach, denoted as local-centric mobility system (LMS), was designed to provide scalability, fast and seamless handovers, and efficient exploitation of network resources and reliability. The LMS can provide handover timings smaller than 100 ms in wireless scenarios, negligible packet loss during handover, and reduced signalling overhead.